The Effectiveness of Law Enforcement by the Police in Addressing Motorcycle Theft Crimes: A Study at the South Sulawesi Regional Police - Ardia Uga Mawarni; Askari Razak; fahri Bachmid (Fakultas Hukum, Universitas Muslim Indonesia, 2026)
This study aims to analyze the effectiveness of police functions in law enforcement against motorcycle theft within the jurisdiction of the South Sulawesi Regional Police. The research employs an empirical juridical approach by examining the implementation of law in practice through field data and legal analysis. Data were obtained from interviews with police investigators, documentation studies, and relevant legal materials. The findings indicate that police functions, including preemptive, preventive, and repressive measures, have been implemented but have not yet achieved optimal effectiveness. This is reflected in the gap between the number of reported cases and the rate of case resolution. Several factors influence this condition, including the consistency of legal regulations, the professionalism and integrity of law enforcement officers, limitations in facilities and infrastructure, low community participation, and the level of legal culture within society. The study emphasizes the importance of strengthening institutional capacity, utilizing technology, enhancing community involvement, and reformulating adaptive law enforcement strategies. These efforts are expected to improve the effectiveness of law enforcement and contribute to maintaining public security and order